2018
DOI: 10.1111/pan.13525
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen pharmacokinetics in severely obese adolescents and young adults

Abstract: Background Intravenous acetaminophen is commonly administered as an adjunctive to opioids during major surgical procedures, but neither the correct pharmacokinetic size descriptor nor the dose is certain in severely obese adolescents undergoing bariatric surgery. Methods Adolescents, 14‐20 years of age, with a body mass index (BMI) ≥95th percentile for age and sex or BMI ≥40 kg·m−2, presenting for laparoscopic or robotic assisted or vertical sleeve gastrectomy were administered intravenous acetaminophen (1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…One study enrolled male children and adolescents aged 10–17 years with nonalcoholic fatty liver disease (NAFLD) [ 29 ]. The other (single-arm) study enrolled female adolescents aged 14–20 years with morbid obesity [ 26 ]. Therefore, meaningful comparisons could not be made between the pharmacokinetic properties of paracetamol in general populations of overweight/obese versus normal-weight children and adolescents.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…One study enrolled male children and adolescents aged 10–17 years with nonalcoholic fatty liver disease (NAFLD) [ 29 ]. The other (single-arm) study enrolled female adolescents aged 14–20 years with morbid obesity [ 26 ]. Therefore, meaningful comparisons could not be made between the pharmacokinetic properties of paracetamol in general populations of overweight/obese versus normal-weight children and adolescents.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…In a single-arm clinical trial, Hakim and colleagues [ 26 ] evaluated the pharmacokinetics of a single dose of paracetamol 1000 mg in 11 female adolescents with morbid obesity (mean BMI = 46 kg/m 2 , standard deviation 5 kg/m 2 ) aged 14–20 years. Observed data and simulated pharmacokinetic modeling demonstrated that a two-compartment model using allometric scaling provided the best fit to the observed data.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Intravenous (IV) acetaminophen has a role in managing fever and postoperative pain, in order to minimize or avoid opiates. Hakim et al (20) recruited 11 adolescent girls with severe obesity and administered a single 1,000‐mg IV dose following bariatric surgery. Subsequent serum acetaminophen concentrations, < 30 µmol/L (4.5 µg/mL), were inadequate for analgesia.…”
Section: Findings and Discussion By Therapeutic Categorymentioning
confidence: 99%